Export-led growth and growth-led export in ASEAN: A panel VECM causality analysis - Suripto, Suripto; Khasanah, Uswatun; Sukarniati, Lestari; Salim, Agus; Kurniawan, Mahrus Lutfi Adi; Athfal, Azkal Azkiya (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the bidirectional relationship between exports and economic growth in five ASEAN countries: Indonesia, Malaysia, Thailand, Singapore, and the Philippines. The analysis applies the Export-Led Growth (ELG) and Growth-Led Export (GLE) frameworks using annual panel data from 1971 to 2023. The Vector Error Correction Model (VECM) and panel Granger causality tests are employed to identify short-term dynamics and long-term equilibrium relationships. Stationarity is tested using the Levin-Lin-Chu, Im-Pesaran-Shin, and Phillips-Perron methods, while long-run cointegration is examined using the Kao and Pedroni approaches. The findings confirm a stable long-run relationship between exports and economic growth across ASEAN countries. In the short run, causal directions vary among countries. The Export-Led Growth pattern appears in Indonesia, Singapore, and Thailand, whereas the Growth-Led Export pattern is evident in the Philippines, while Malaysia shows a weaker short-term interaction. Long-run estimates reveal a two-way adjustment mechanism between exports and growth, suggesting that structural differences and trade openness determine the strength and direction of causality. The novelty of this research lies in the simultaneous testing of ELG and GLE hypotheses within a panel-based VECM framework that integrates short-run and long-run dynamics using Python-based econometric modelling. The study contributes new empirical evidence and policy insights for designing context-specific trade and growth strategies across ASEAN economies.